A chloroplast genome sequence of Viola arcuata distributed in Korea. Issue 9 (2nd September 2022) - Moon, Hyeonji; Kim, Sangtae
Abstract: Recently, the chloroplast genome of Viola verecunda from a sample collected in Japan has been published. Although the name is often recognized as a taxonomic synonym of Viola arcuata, the genetic identity of the two species has never been compared intensively. We report the complete chloroplast genome sequence of V. arcuata, of which sample was collected from Seoul, Korea. The cp genome of V. arcuata (OM301625) has 157, 870 bp in length and is composed of four regions: 86, 366 bp of a large single-copy (LSC) region, 17, 298 bp of a small single-copy (SSC) region, and 27, 103 bp of a pair of inverted repeats (IRs). The complete genome contains 130 genes, including 84 protein-coding genes, eight rRNA genes, and 37 tRNA genes. When comparing chloroplast genomes between V. verecunda, and V. arcuata, 34 different loci were recognized: 12 SNPs and 22 indels. In the coding regions, there were two amino acid insertions ( ndhI ) caused by one base deletion, three synonymous substitutions ( ndhF, ccsA, and ndhI ), and six nonsynonymous substitutions ( matK, rpoC2, ndhF, ycf1, and two rpl2 s on each IR region). In non-coding regions, variants of 19 polyN sites, one microsatellite, two insertions, and two SNPs were recognized. Phylogenetic analysis confirms a sister or nearly identical relationship between two genomes. This study will provide the genetic basis for solving a taxonomic problem between V. arcuata and V. verecunda .